Robotics technology : automatic guided vehicle (Shopware, 2004)
Industrial production has been revolutionized by the use of automated technology. This program looks at the many types of industrial equipment used in a paper mill, and highlights the use of Automatic Guide Vehicles to load and transport newsprint rolls. The AGV is a wireless robot that can carry 4000 lbs. safely and effectively at a rate of 200 feet per minute. Shown completing various tasks, AGVs give viewers a greater appreciation and understanding of how automation has increased production capabilities